2004
DOI: 10.1007/bf02830827
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity — Risk factors

Abstract: Indirect ophthalmoscopy should be performed at 4 weeks of post natal age in all preterm babies with birth weight < or = 1500 gm, and intensified in the presence of risk factors like oxygen administration, apnoea and septicemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
89
2
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 14 publications
17
89
2
5
Order By: Relevance
“…Similar results were shown by Agarwal et al and Gupta et.al 25,23 . In the present study, oxygen duration >10 days, C-PAP and ventilation were found to be significant risk factor on univariate analysis similar to results shown by shah et al in their study on ROP in 2005 28 .…”
Section: Resultssupporting
confidence: 89%
“…Similar results were shown by Agarwal et al and Gupta et.al 25,23 . In the present study, oxygen duration >10 days, C-PAP and ventilation were found to be significant risk factor on univariate analysis similar to results shown by shah et al in their study on ROP in 2005 28 .…”
Section: Resultssupporting
confidence: 89%
“…3 In our country, the incidence of ROP is reported to approximately range from 20 to 52% in preterm infants. [4][5][6][7][8] Changes in neonatal care have increased the survival of preterm infants and decreased the gestational age at which preterm born infants are kept 1 Department of Paediatrics, 2 Department of Ophthalmology, Dr. Sampurnanand Medical College, Jodhpur, Rajasthan, India alive, resulting in an increasing number of infants at risk for ROP. Previous studies have stated certain risk factors like prolonged oxygen therapy, anaemia needing blood transfusion, sepsis, apnoea and few others which increase the probability of developing ROP.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have stated certain risk factors like prolonged oxygen therapy, anaemia needing blood transfusion, sepsis, apnoea and few others which increase the probability of developing ROP. [4][5][6][7][8] Visual impairment can be decreased by timely screening, thorough follow up and prompt treatment of neonates who are diagnosed with ROP and offer better overall development for the child. 9 So, a dedicated screening program is indispensable.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted at University Medical College, GTB Hospital, Delhi by Gupta et al 6 revealed Septicemia exchange transfusion, Hyaline membrane disease and Apnea as significant risk factor for ROP.…”
Section: Discussionmentioning
confidence: 99%